SEHATIKA: A Thematic Learning Model with Science Literacy to Enhance Clean and Healthy Living Behavior in Early Childhood - Rizka, Nelti; Jalal, Fasli; ., Yufiarti (Journal of Cultural Analysis and Social Change, 2025)
This study aims to develop a thematic learning model integrated with science literacy to improve clean and healthy living behavior (PHBS) among early childhood students. The research employs a mixed-method approach using the Borg & Gall development model combined with the ADDIE instructional design framework. Findings indicate that the proposed model significantly enhances students' understanding and implementation of PHBS behaviors, including handwashing, healthy eating, oral hygiene, physical activities, and waste disposal. The study highlights the importance of integrating science literacy into early childhood education to foster sustainable health habits. Implications for educators and policymakers are discussed.